Ungkapan dalam Upacara Tradisional Perkawinan Suku Jawa - Wiwiek Sundari (KAJIAN SASTRA, 2008)
Javanesse people keep preserving Javanesse traditions inwedding ceremonies. The traditions are represented in sets ofceremonies such as siraman, ijab kabul, panggih, In each ceremony,Javanesse people use particular expressions. The expressions are inthe form of words and phrases which have functions to convey aparticular meaning that is meant to give advice to the newly marriedcouple,Keywords: : tradition, wedding ceremony, expressions, words,phrases, couple